2019
DOI: 10.1002/nem.2063
|View full text |Cite
|
Sign up to set email alerts
|

Game of protocols: Is QUIC ready for prime time streaming?

Abstract: SummaryQuick User Datagram Protocol (UDP) Internet Connections (QUIC) is an experimental and low‐latency transport protocol proposed by Google, which is still being improved and specified in the Internet Engineering Task Force (IETF). The viewer's quality of experience (QoE) in HTTP adaptive streaming (HAS) applications may be improved with the help of QUIC's low‐latency, improved congestion control, and multiplexing features. We measured the streaming performance of QUIC on wireless and cellular networks in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…On the other hand, a performance investigation similar to that of [24] was conducted in [26] with the Google QUIC server v39. The finding in [26] showed that, while the HAS clients running over QUIC could perform fairly against one another, they provided 37% higher bitrate than the HAS over TCP clients in most cross-protocol cases.…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, a performance investigation similar to that of [24] was conducted in [26] with the Google QUIC server v39. The finding in [26] showed that, while the HAS clients running over QUIC could perform fairly against one another, they provided 37% higher bitrate than the HAS over TCP clients in most cross-protocol cases.…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, there also have been a few attempts to investigate such a problem of the HAS/3. Specifically, due to the potential unavailability of the HTTP/3 due to the UDP nature of its transport QUIC, many works have focused on the cross-protocol scenario where HAS/3 clients compete with HAS/2 and/or HAS/1.1 clients 9,10,11 . Nevertheless, those works only provide observations of the general non-fairnessaware ABRs.…”
Section: Introductionmentioning
confidence: 99%